Моніторинг атмосферного повітря. Проблеми моделювання і прогнозування - Трофімович, В.В.; Волошкіна, О.С.; Фандікова, М.М.; Клімова, І.В.; Журавська, Н.Є. (My University, 2012)
High level of chemicals such as formaldehyde, nitrogen oxide and all kind of dust are present in the atmosphere of most of the cities of Ukraine. However there is no formaldehyde found in general sorces of air pollution like stationary sources (power plants) and modile sources (motor vechcles) emmisions. Studies in large sities like Kiev, Donechk or Luchk show that formation and concentration of formaldehyde in atmosphere changing from low to high depends of weather, anount of sunny and cloudy days and time of the year as a result of photochemical reaction. The presence of formaldehyde in the atmosphere can be assumed as a safety indicator of air pollution and can be used prognose function.
Keywords: моніторинг; атмосферне повітря; екологічна безпека